If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = -10x + 4 Reorder the terms: 2y = 4 + -10x Solving 2y = 4 + -10x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 2 + -5x Simplifying y = 2 + -5x
| -7=9x+16-10 | | 2(x+p)=3(6p-x) | | 9k-3k=30 | | 3y+4=y+18 | | -44-1x=28-4x | | x-7.1=-6.2 | | -(3y+1)-(-2y-7)=2 | | 96-2x=43x+16 | | 7(7x-3)+10x= | | 2x+80=158 | | 5p-3=32 | | 3x=3x+2 | | x=.4+(-.2y) | | B-2+6B=27 | | 3x/4=6 | | 6x-11x+4=0 | | 13x^2+1-[7(x^2-8)+5]= | | 6x^7-18x^4+24x^6= | | 6+2y-2=9y+13-6y | | 14(t-3)+4t=6(3t+3)-10 | | 2x-5=x+7+2x | | 5fg+g^2=0 | | 2x+-.5=-.75 | | 5fg+g^2=03 | | 7x+15=29 | | 7a+21b=35 | | 3*4=10 | | 5x+7=25-x | | 9x-10=34-2x | | 2xX+-.5=-.75 | | -12x+5=17 | | 7a+21b=36 |